2014
DOI: 10.1016/j.micinf.2014.02.006
|View full text |Cite
|
Sign up to set email alerts
|

A critical review of social and structural conditions that influence HIV risk among Mexican deportees

Abstract: Mexican migrants who are deported from the US may be at elevated risk for HIV infection. Deportations of Mexican migrants by the US have reached record numbers. We critically reviewed existing literature to assess how social and structural conditions in post-deportation settings can influence Mexican deported migrants' HIV risk. We also identify critical research gaps and make research recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 37 publications
1
42
0
Order By: Relevance
“…Tijuana also has a prominent population of migrants, primarily men, who have been deported from the United States and have resettled in Tijuana (Pinedo et al, 2014b(Pinedo et al, , 2015; the city received~316,000 deported migrants between (Instituto Nacional de Migracion, 2011, 2013. Migrants are highly stigmatized in Tijuana, where they are perceived by the community as the cause of prevailing social problems, including increasing rates of crime and drug use (Infante et al, 2012;Pinedo et al, 2014a). Sociocultural and visual differences (e.g., clothes, speech) may quickly distinguish migrants from locals (Infante et al, 2012;Pinedo et al, 2014a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tijuana also has a prominent population of migrants, primarily men, who have been deported from the United States and have resettled in Tijuana (Pinedo et al, 2014b(Pinedo et al, , 2015; the city received~316,000 deported migrants between (Instituto Nacional de Migracion, 2011, 2013. Migrants are highly stigmatized in Tijuana, where they are perceived by the community as the cause of prevailing social problems, including increasing rates of crime and drug use (Infante et al, 2012;Pinedo et al, 2014a). Sociocultural and visual differences (e.g., clothes, speech) may quickly distinguish migrants from locals (Infante et al, 2012;Pinedo et al, 2014a).…”
Section: Discussionmentioning
confidence: 99%
“…Migrants are highly stigmatized in Tijuana, where they are perceived by the community as the cause of prevailing social problems, including increasing rates of crime and drug use (Infante et al, 2012;Pinedo et al, 2014a). Sociocultural and visual differences (e.g., clothes, speech) may quickly distinguish migrants from locals (Infante et al, 2012;Pinedo et al, 2014a). Recent migrants who are PWID may be less acclimated to the local culture and environment, thus quickly identifiable and vulnerable to police victimization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deportation from the US can be a traumatic experience. Post-deportation, migrants experience multiple social, emotional, and economic stressors that impact their physical and mental health (Pinedo, Burgos, & Ojeda, 2014). Two recent studies conducted among deported migrants in the US-Mexico border region suggest that deportees display an elevated prevalence of depressive symptoms and mental health problems as compared to the general population and migrants without a history of deportation (Bojorquez, Aguilera, Ramírez, Cerecero, & Mejía, 2014; Bojorquez, Mejia, Aguilar, Cerecero, & Albicker, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies were not exclusive to deportees who inject drugs, our primary population of interest. In qualitative studies in Tijuana, deported PWID allude to their poor emotional state as influencing their decisions to participate in high-risk activities (e.g., initiating injection drug use, drug relapse, experimenting with new drugs, paying for sex) (Goldenberg et al, 2011; Goldenberg, Strathdee, Gallardo, & Patterson, 2010; Ojeda et al, 2011; Pinedo, Burgos, & Ojeda, 2014; Robertson, Lozada, et al, 2012). Another study among deported male PWID in Tijuana reported that feeling sad following the most recent deportation was independently associated with trying new drugs post-deportation (Robertson, Rangel, R. Lozada, Vera, & Ojeda, 2012).…”
Section: Introductionmentioning
confidence: 99%